2016
DOI: 10.3389/fbioe.2016.00074
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioconversion of Pyruvate to n-Butanol with Minimized Cofactor Utilization

Abstract: Due to enhanced energy content and reduced hygroscopicity compared with ethanol, n-butanol is flagged as the next generation biofuel and platform chemical. In addition to conventional cellular systems, n-butanol bioproduction by enzyme cascades is gaining momentum due to simplified process control. In contrast to other bio-based alcohols like ethanol and isobutanol, cell-free n-butanol biosynthesis from the central metabolic intermediate pyruvate involves cofactors [NAD(P)H, CoA] and acetyl-CoA-dependent inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Besides acting as an important enzyme for ethanol production, PDC has also been applied in the in vitro production of nbutanol (Scheme 1). 10,11 Butanol together with other longerchain alcohols, such as 1-propanol, isobutanol and Scheme 1 Simplified pathway to produce ethanol and 1-butanol from lignocellulosic biomass via pyruvate decarboxylase (PDC). There are two major pathways for producing 1-butanol via pyruvate: CoAdependent or proline-dependent condensation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides acting as an important enzyme for ethanol production, PDC has also been applied in the in vitro production of nbutanol (Scheme 1). 10,11 Butanol together with other longerchain alcohols, such as 1-propanol, isobutanol and Scheme 1 Simplified pathway to produce ethanol and 1-butanol from lignocellulosic biomass via pyruvate decarboxylase (PDC). There are two major pathways for producing 1-butanol via pyruvate: CoAdependent or proline-dependent condensation.…”
mentioning
confidence: 99%
“…17,18 This effect, however, is less pronounced for the enzymes catalysing butanol production in vitro. 10,19 Many enzymes can already tolerate higher organic solvent concentrations than the corresponding microorganisms. 20 Furthermore, engineering enzyme stability towards organic solvents is less challenging than evolving microorganisms to withstand the same concentration of organic solvents.…”
mentioning
confidence: 99%
“…Having both keto and carboxylic groups in its structure, pyruvate is a potential precursor for many chemicals, pharmaceuticals, food additives, and polymers. For example, pyruvate has been used in the biochemical synthesis of L-DOPA [1], N-acetyl-D-neuraminic acid [2], (R)-phenylacetylcarbinol [3], butanol using a three-enzyme cascade [4], and has been proposed as a starting material for the enzymatic synthesis of propionate [5]. A recent assessment of Escherichia coli as a cell factory concluded that pyruvate was one of the most useful metabolic precursors to a wide range of non-native commercial products [6].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, various strategies have been investigated, including: strain modifications to improve butanol tolerance, in vitro production using immobilized enzymes, and fermentation process developments to remove the butanol from the fermentation broth as it is produced have been developed . Via such product removal techniques, the butanol concentration in the fermentation broth will be maintained below inhibitory levels, leading to increased productivity and overall titers.…”
Section: Introductionmentioning
confidence: 99%
“…5 This is compounded by the complex separation of butanol from water due to the azeotrope forming at 55.5 wt% butanol at 101.3 kPa. 6 To overcome these problems, various strategies have been investigated, including: strain modifications to improve butanol tolerance, 2,4 in vitro production using immobilized enzymes, 7 and fermentation process developments to remove the butanol from the fermentation broth as it is produced have been developed. 2 Via such product removal techniques, This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%